ANALISIS TINGKAT KEBISINGAN TERHADAP STANDAR BAKU MUTU TINGKAT KEBISINGAN DI RUMAH SAKIT MESRA KABUPATEN KAMPAR TAHUN 2020: ANALYSIS OF NOISE LEVEL OF QUALITY RAW STANDARD STANDARDS IN THE MESRA HOSPITAL IN KAMPAR DISTRICT, 2020 - M Erizal; Makomulamin Makomulamin (Progam Studi Kesehatan Masyarakat STIKes Hang Tuah Pekanbaru, 2021)
High noise levels in hospitals can contribute to stress and fatigue in hospital staff, reducing the speed of healing of patients. Noise level measurement is in accordance with the existing quality standard in Permenkes No. 7 of 2019 in Mesra Hospital, Kampar Regency, there are several rooms that exceed the predetermined standard values. The purpose of this study was to determine the level of noise against quality standards at Mesra Hospital in Kampar Regency. This type of research is descriptive qualitative. Interviews and observations were conducted to 5 informants through in-depth interviews. The location of the study was conducted at the Mesra Hospital of Kampar Regency in May-July 2020. The results of the study and the measurements made showed that in front of the intimate hospital had a high noise level such as the lobby during the day the measurements were made with 69 dBA results, for the results of corridor measurements / which hall from the measurement results during the day produces a value of 67 dBA, and the results of measurements during the day in the medical record room produces a value of 67 dBA. From observations and interviews with informants it was found that in handling noise levels were inadequate such as the absence of standard operating procedures regarding noise handling, as well as the absence of printouts of noise measurements that had been carried out and also the lack of noise control at the front of the mesra hospital. Still the loud voice of a traffic vehicle inside the lobby was caused by the lack of tree planting in the front of the mesra hospital.